(untitled) (ASEAN Engineering Journal, 2011)
During Paleozoic-Mesozoic times, the Eastern Indonesia region is considered to be a part of the northern margin of the Australian continent which has now become an active collisional margin. Stratigraphic sections, of Eastern Indonesia at least from Cambrian to Paleogene, show similarities which document two tensional tectonics episodes; an Early Paleozoic infra-rift and a Late Paleozoic to Paleogene rift. Since Miocene times, sedimentary rocks indicate a series of subduction and collision products. The succession of pre-Tertiary sediments in Eastern Indonesia mostly developed unconformbly, overlying the highly metamorphic rocks of Devonian to Permian which are considered as the basement. In the Outer Banda Arc to the Sula-Buton region, pre-Tertiary sedimentary rocks were characterized by a series of carbonate rocks, which developed up to Tertiary times. In contrast, the Papua (Irian Jaya) region was marked by the dominance of siliciclastic rocks during the Paleozoic to Mesozoic and carbonate rocks and shale in Tertiary. Pre-Tertiary and Tertiary sedimentary rocks in some basins of Eastern Indonesia are proven as hydrocarbon producers. Although pre-Tertiary source rocks are widespread in Eastern Indonesia, the significant example were primarily restricted to three time periods; Permian, Late Triassic and Early-Middle Jurassic. The Reservoir rocks mainly belong to the Mesozoic and Tertiary ages, where sandstone and carbonate rocks developed in the Mesozoic and in the Tertiary were dominated by Miocene limestone and sandstones, and Pliocene sandstones. Traps are mainly controlled by thrust faults, normal faults and carbonate buildup, while the syn-orogeny and passive margin shales provide seal rocks.